A study on factors that affect the customer usage of KTM Berhad intercity train services / Khairunnisa Halid - Halid, Khairunnisa (Faculty of Business and Management, 2006)
From year 1992 until 2003 the number of passengers KTM Berhad intercity train services decreased year to year. The purpose of study is to identify the factors that affect the customer usage of KTM Berhad intercity train services. The factors can be measure on the weaknesses of KTM Berhad intercity train services.